Initiating a Full Fulfill-Based Deep Learning-Based Curriculum: Integration of Knowledge and Character in Learning - Fitri, Aulia; Amin, Khairul; Tauhid, Zuhri; Ramadona, Aulia; Wismanto, Wismanto (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
An effective educational curriculum must be able to integrate the development of students' knowledge and character, especially in facing the challenges of the modern era. Based on these needs, the Full Fulfill curriculum  was developed to combine aspects of academic knowledge with character formation through in-depth learning approaches, namely Mindful Learning, Meaningful Learning, and Joyful Learning. The purpose of this study is to explore the effectiveness of the Full Fulfill curriculum  in improving the quality of learning and shaping students' character through the habit of positive behavior, such as healthy living habits and society. This approach is designed so that students not only receive theoretical knowledge, but also engage in holistic self-development, which includes physical, social, and emotional aspects. This study uses a descriptive qualitative method, with data collected through observation, interviews, and document analysis. The sample consisted of students and teachers at several schools that have implemented this curriculum. Data analysis was carried out by referring to the theories of character education and active learning approaches to ensure the relevance and success of the curriculum. The results of the study show that the Full Fulfill curriculum  is effective in facilitating students to learn deeply and form good habits, such as the habit of waking up early, worshipping, exercising, loving to study, eating healthy, socializing, and sleeping on time. In addition, five main strategies—counseling guidance training, teacher competency improvement, character building, appointment of BK teachers, and a nutritious lunch program—play a significant role in supporting the implementation of this curriculum. The Full Fulfill curriculum  offers a holistic approach, emphasizing a balance between knowledge and character building in a supportive educational environment. These findings contribute to the development of a modern curriculum that is more adaptive to the needs of today's students, with the hope that this curriculum can be widely applied to achieve sustainable and holistic educational outcomes.